Water stress and warming impact nutrient use efficiency of Mombasa grass (Megathyrsus maximus) in tropical conditions - Olivera Viciedo, Dilier [UNESP]; de Mello Prado, Renato [UNESP]; Martinez, Carlos A.; Habermann, Eduardo; Branco, Roberto Botelho Ferraz; de Cássia Piccolo, Marisa; Calero Hurtado, Alexander [UNESP]; Peña Calzada, Kolima [UNESP]; Lata Tenesaca, Luis F. [UNESP] (Wiley, 2021)
Temperature and other abiotic factors, such water and nutrient availability, play an important role for plants in response to the changing environments. At this regard, both warming and drought might affect the nutrient use efficiency (NUE) and growth of Megathyrsus maximus a C4 forage grass of high interest for cattle feeding. However, the nutrient requirements of this species under climate change are unknown. Therefore, we aimed to evaluate the individual and combined effects of two levels of temperature: ambient and elevated temperature (2°C above ambient temperature), and two levels of soil water availability: irrigated plants and non-irrigated plants on accumulation of leaf nutrients, NUE and biomass production of M. maximus. Temperature control was performed by a temperature free-air-controlled enhancement (T-FACE) system under field conditions. In general, we observed that warming under well-irrigated conditions increased the leaf accumulation of most nutrients, improving the NUE of N, P, K, Ca, Mg, Cu, Mn and Zn. Plant growth was also enhanced under warming effects, with higher leaf dry mass accumulation and root development. Meanwhile, drought decreased NUE of K, Ca, B and leaf dry biomass, while root growth was stimulated. The combined effects of warming and drought on nutrient accumulation, NUE and plant growth tended to be greater than the individual effects expected from a single factor; thus, warming mitigated the negative impacts of individual drought. In summary, our findings suggest that warming and drought, both as individual and combined factors, will change the nutrient requirements of M. maximus in tropical ecosystems.
Keywords: C4 pasture; elevated temperature; forage; global climate change; nutrient uptake; root growth